Dicks or Hearts. What Can Modern Wall Self-expression Tell us? - Zagorov, Vasil (BBDS - Black Book: Drawing and Sketching, 2023)
The article looks at modern graffiti, in the widest sense of understanding this notion, as a means of studying the prehistoric rock art. Based on the case study approach, a number of locations have been presented of self-expression of modern humans, which are current conveniently forgotten by civilized people practices of the past of human civilization. The object of research is a city wall, which has been a mediator of an active process of written and visual communication for the last decade. An analysis has been made of the means of expression, the motifs and techniques of the messages. Based on this study, the potential of such objects to help the research in the field of prehistoric rock art is present. A series of questions have been posed that can be useful when applying the contemporary methods of studying the early steps of visualizing human thought.